Regulation of reactive oxygen species and phytohormones in osmotic stress tolerance during seed germination in indica rice - Kawaguchi, Ryusuke; Suriyasak, Chetphilin; Matsumoto, Ryo; Sawada, Yuta; Sakai, Yuki; Hamaoka, Norimitsu; Sasaki, Kazuhiro; Yamane, Koji; Kato, Yoichiro; Bailly, Christophe; Ishibashi, Yushi (Frontiers in Plant Science, 2023)
Climate change due to global warming is now affecting agricultural production worldwide. In rice, one of the most important crops, water limitation due to irregular rainfall in rainfed lowlands during crop growth limits yield. Dry direct-sowing has been proposed as a water-efficient approach to cope with water stress during rice growth, but poor seedling establishment due to drought during germination and emergence is a problem. Here, we germinated indica rice cultivars Rc348 (drought tolerant) and Rc10 (drought sensitive) under osmotic stress induced by PEG to elucidate mechanisms of germination under drought. Rc348 had higher germination rate and germination index under severe osmotic stress of −1.5 MPa, above those of Rc10. Rc348 showed up-regulated GA biosynthesis, down-regulated ABA catabolism, and up-regulated α-amylase gene expression in imbibed seeds under PEG treatment compared to that of Rc10. During germination, reactive oxygen species (ROS) play important roles in antagonism between gibberellic acid (GA) and abscisic acid (ABA). Embryo of Rc348 treated with PEG had significantly greater expression of NADPH oxidase genes and higher endogenous ROS levels, together with significantly increased endogenous GA1, GA4 and ABA contents compared to that of Rc10. In aleurone layers treated with exogenous GA, expression of α-amylase genes was higher in Rc348 than in Rc10, and expression of NADPH oxidase genes was enhanced with significantly higher ROS content in Rc348, suggesting higher sensitivity of GA to ROS production and starch degradation in aleurone cells of Rc348. These results suggest that the osmotic stress tolerance of Rc348 is due to enhancement of ROS production, GA biosynthesis, and GA sensitivity, resulting in a higher germination rate under osmotic stress.